Kawaii Bunka dalam Vlog Visiting Japanese Maid Cafe @Home Cafe Akihabara - Zahroh, Indah Fajriyatus; Sari, Venita Putri Ardiani Permata; Rahma, Nabila Ainur; Azizah, Nurul; Fairuzzahra, Nabila Vina (Japanology: The Journal of Japanese Studies, 2023)
Kawaii bunka is about something that has cute, funny and childish impression. The concept of kawaii bunka is not only found in anime and manga characters, but is also shown in maid cafes in Japan, in which one of the most popular maid cafe in Japan is @Home Cafe Akihabara. This research aims to examine what kind of forms of kawaii bunka that can be found in @Home Cafe Akihabara through Visiting Japanese Maid Cafe | @Home Cafe Akihabara | ASMR vlog. This research is descriptive qualitative research and uses theory of kawaii bunka by Kinsella. The result of this research shows that kawaii bunka in @Home Cafe Akihabara is reflected through the maid's handwriting in polaroid photos, the uniforms worn by the maids, the food and drinks served, the behavior and identity of the maids, the demographics of the waiters and visitors who come, and the products and services offered by @Home Cafe Akihabara. These aspects emphasize childish sentiments, so it can be understood that there is a narrative in which maid cafes are places where visitors can feel and act childishly.